A Return to Tohunga Suppression Act 1907 - Stephens, Māmari (Victoria University of Wellington Law Review, 2001)
In this article the author revisits the Tohunga Suppression Act 1907 to provide a fresh analysis of the rationale for its passage and subsequent operation. The author challenges the traditional of the passage of the Act as a catalyst to improve Maori health and as a political weapon against the prophet Rua Kenana. Rather, the author suggests that the primary intent of the Tohunga Suppression Act was to assert certainty and political dominance at a time both were seen to be absent. The motives of the Maori members in supporting the passage of the bill are also discussed. The article further analyses the operation of the Act. In particular, the pivotal role of the Maori Councils in giving effect to the Act is highlighted as is the cautious approach of the judiciary. In light of these aspects of the Act’s operation, the author questions the effectiveness of the Act in achieving its proponents aims.